Comportamiento fisiológico y crecimiento de plántulas de café (Coffea arabica L.), bajo cuatro niveles de humedad del sustrato en la quinta experimental docente La Argelia - Namicela Romero, Jenny Patricia (2016)
This research work was carried out in the greenhouse of Área Agropecuaria y de Recursos Naturales Renovables de la Universidad Nacional de Loja, in order to evaluate the physiological behavior and the growth of coffee seedlings under four levels of soil moisture. Humidity levels evaluated were H1: 10-15 cb; H2: 25-30 cb; H3 and H4 40-45 cb: 55-60 cb, these voltage ranges, were maintained refilling the volume of water required, based on readings of sphygmomanometers that were placed in each treatment. Evaluations were made monthly from 33 days after transplantation in bags (DDT the evaluated variables were: height, stem diameter, stomata density and stomata width. In addition, leaf area at 63, 93 and 123 DDT was evaluated. In addition, leaf area at 63, 93 and 123 DDT was evaluated and at the end of the experimental period the dry mass of air, radical and total part, root length, relative water content and chlorophyll content was evaluated The highest values in terms of height, stem diameter, leaf area, dry mass of shoot and root, total dry mass, root length, relative content of water and width of stomata were presented at the moisture levels H1 and H2 substrate; regarding the stomata density higher values presented at moisture levels respectively H3 and H4; on the content of chlorophyll was no significant difference between treatments were presented. The volume of water used in each treatment was calculated based on the moisture content of the given substrate gravimetric method (based on weight) and the root depth of seedlings, same that was increased in each evaluation and based on levels moisture. It was concluded that growth, expressed in indicators such as height, stem diameter, leaf area, root length, dry mass of seedlings in all treatments presented a direct relationship with the moisture content of the substrate; while H1 and H2 treatments remained similar results within the variables evaluated, allowing use of lower humidity level (H2) without leading to slow seedling growth and generating savings of 6.24 l of water volume used.